2022
DOI: 10.3389/fenrg.2022.857948
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Large-Scale Solar PV Plant Energy Performance–Loss–Degradation in Coastal Climates of India

Abstract: This article presents a detailed analysis of the performance, rate of degradation, and power and energy loss of a 1 MWp scale solar photovoltaic (PV) plant in the academic institution GITAM (Deemed to be University), located in the coastal region of Andhra Pradesh, India. The PV plant consists of 3,078 polycrystalline PV modules of 325 Wp rating, installed on the rooftop of the institute buildings. The annual energy generated is 1684.881 MWh. In this study, performance analysis involves the calculation of effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…The temperature losses are 6.2%, irradiance losses are 0.4%, mismatch losses are 4.0%, soiling losses are 2.0%, electrical wiring losses are 0.3%, reflection losses are 3.2%, clipping losses are 0.0%, shading losses are 0.4%, inverter losses are 3.0%, and AC system losses are 0.5%. The losses in this research are lower than losses in the research study (Navothna and Thotakura, 2022). The annual energy generation and performance ratio of the PV system decline as the percentage of soiling losses and temperature of the site increases.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The temperature losses are 6.2%, irradiance losses are 0.4%, mismatch losses are 4.0%, soiling losses are 2.0%, electrical wiring losses are 0.3%, reflection losses are 3.2%, clipping losses are 0.0%, shading losses are 0.4%, inverter losses are 3.0%, and AC system losses are 0.5%. The losses in this research are lower than losses in the research study (Navothna and Thotakura, 2022). The annual energy generation and performance ratio of the PV system decline as the percentage of soiling losses and temperature of the site increases.…”
Section: Discussionmentioning
confidence: 49%
“…The simulation model of the photovoltaic power generation is developed by taking different parameters under consideration. The simulation results of a designed photovoltaic system showed that the annual energy generation is 15.79 MWh and the performance ratio (PR) is 88.1%, the performance ratio in this research is high as compared to the research study (Navothna and Thotakura, 2022), and the power generation (kWh/kWp) is 1548.2. The maximum monthly energy production is 1,708.2 kWh, the maximum global horizontal irradiance (GHI) is 204.4 kWh/m 2 , and the maximum plane of array irradiance (POA) is 206.3 kWh/m 2 in May.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…This inspection is performed in accordance with the standard of IEC 61215-1. After visual inspection, an on-field test methodology based on Solar V-I curve tracer [12][13][14] was carried out for a short-term duration for formulation of a cost effective design tool for estimating performance loss rate or degradation rate. An on-field Solar IV curve tracer, PV 200 was employed for measurement.…”
Section: Solar V-i Curve Tracer Based On-field Experimentation For As...mentioning
confidence: 99%
“…The massive burning of mineral energy has caused global environmental pollution and ecological destruction, including the extreme overheating of the environment (Ma et al, 2021;Arsalan et al, 2022;Zakari et al, 2022). Solar energy is a free and environmentally friendly supply of power that has a negligible impact on the environment (Almutairi, et al, 2021) and has tremendous potential to replace fossil fuels with secure, clean, and sustainable energy (Trancik et al, 2015;Navothna and Thotakura, 2022). Many nations, such as the United States, Spain, Morocco, India, and China, have implemented solar energy systems in their electrical grids (Soomar, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%